1996
DOI: 10.1007/bf00189056
|View full text |Cite
|
Sign up to set email alerts
|

Optical measurement of liquid film thickness and wave velocity in liquid film flows

Abstract: helped build the laboratory facilities. The ACRC receives continuing support from the Richard W. Kritzer Endowment and the National Science Foundation. The following organizations have also become sponsors of the Center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…This larger data set has more scatter, but the general trend seen in figure 4 remains with the correlation significantly stronger than if havg I ho were plotted versus Fr. The data sets showing a more rapid transition towards symmetric annular flow (Hurlburt and Newell (1996) and Jayanti et al (1990» are at the lowest LID's. These flows may not be "fully developed" which is argued by Whalley (1987) to require an LID of about 400.…”
Section: Theory (A) Liquid Film Circumferential Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…This larger data set has more scatter, but the general trend seen in figure 4 remains with the correlation significantly stronger than if havg I ho were plotted versus Fr. The data sets showing a more rapid transition towards symmetric annular flow (Hurlburt and Newell (1996) and Jayanti et al (1990» are at the lowest LID's. These flows may not be "fully developed" which is argued by Whalley (1987) to require an LID of about 400.…”
Section: Theory (A) Liquid Film Circumferential Symmetrymentioning
confidence: 99%
“…Figure 4 is a plot of data taken at one tube diameter and one LID. Figure 5 shows havg I ho vs. (Iilg / rilL) 0.5 Fr for a range of tube diameters and LID's from a variety of different studies (Dallman 1978;Fukano and Ousaka 1989;Hurlburt and Newell 1996;Jayanti et al 1990;Laurlnat 1982;Paras and Karabelas 1991;Williams 1990). This larger data set has more scatter, but the general trend seen in figure 4 remains with the correlation significantly stronger than if havg I ho were plotted versus Fr.…”
Section: Theory (A) Liquid Film Circumferential Symmetrymentioning
confidence: 99%
“…A novel optical technique has been presented that also uses the total internal reflection of light rays to measure the height of liquid films (Hurlburt and Newell;. This method offers many advantages over other measurement techniques: It is non-intrusive; no permanent mounting is required so data can be acquired at any point of a clear test section; any liquid can be measured; no calibration is required since the method is a direct measurement of a signal that is a linear function of the film height; and it is relatively inexpensive and easy to construct.…”
Section: Total Internal Reflection Of Lightmentioning
confidence: 99%
“…It was concluded that the boiling process were dominated by two characteristic periods, i.e., microlayer dominant and liquid saturated periods. Hurlburt & Newell (1996) developed a device which can measure liquid film thickness from total light reflection. Using the same method, Shedd & Newell (2004) measured liquid film thickness of air/water two-phase flow in round, square and triangular tubes.…”
Section: Introductionmentioning
confidence: 99%